2014
DOI: 10.1021/jp510581m
|View full text |Cite
|
Sign up to set email alerts
|

Designing Efficient Azobenzene and Azothiophene Nonlinear Optical Photochromes

Abstract: International audienceThe present contribution constitutes an extensive density functional theory (DFT) investigation of the nonlinear optical (NLO) properties of a large number of molecules belonging to the azobenzene and azothiophene families of photochromic compounds which can act as NLO switches. Toward the design of systems simultaneously presenting both large total nonlinear response values, beta(tot), and large contrast, beta(ratio), between the cis and trans isomers, we have focused not only on the mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 65 publications
2
29
0
Order By: Relevance
“…The search for a DF, describing adequately both energy of excitation and first hyperpolarizability, led to a conclusion that none of the DFs with the account of various degrees of HF exchange was ideal in this sense, although M06‐2X and CAM‐B3LYP, in the author's opinion, come closest to the experimental values. However, range‐separated ωB97X‐D seems to be preferable when just first hyperpolarizabilities are calculated; the same conclusion is made in other papers . In the article by Garza et al by the example of PNA it is shown that the ωB97X‐D functional gives hyperpolarizability values in good agreement with experiment, the error depending upon the choice of the basis set and being less than 10%.…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…The search for a DF, describing adequately both energy of excitation and first hyperpolarizability, led to a conclusion that none of the DFs with the account of various degrees of HF exchange was ideal in this sense, although M06‐2X and CAM‐B3LYP, in the author's opinion, come closest to the experimental values. However, range‐separated ωB97X‐D seems to be preferable when just first hyperpolarizabilities are calculated; the same conclusion is made in other papers . In the article by Garza et al by the example of PNA it is shown that the ωB97X‐D functional gives hyperpolarizability values in good agreement with experiment, the error depending upon the choice of the basis set and being less than 10%.…”
Section: Resultssupporting
confidence: 57%
“…At present the number of works dealing with the calculations of molecular polarizabilities of stacked clusters is essentially fewer than those where the energy of binding π–π interactions is studied. As a rule the choice of an adequate computational level was done by the example of isolated chromophores . To select the calculation method to be used for reliable NLO characteristics estimation for both isolated chromophores and stacked clusters, it is necessary to come to an agreement on the reference data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aromatic azo compounds are widely used in the chemical industry as dyes, pigments [6][7][8], food additives [9], indicators [10], radical reaction initiators [11] and therapeutic agents [12,13]. In addition, azobenzenes have shown promising applications in photo-optical media [14], photo-switches [15], photo-mechanical systems [16], micro patterning [17], nonlinear optical media [18], molecular shuttles, [19] nanotubes, [20] and in the manufacture of protective eye glasses and filters [21]. Moreover, the light induced reversible isomerization of azobenzenes between cis and trans forms makes them excellent candidates to modulate the relative movement of different moieties; thus leads to the development of light driven motors [22].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] In particular, much effort has recently been invested in designing molecules with a large two-photon absorption strength (δ TPA ) -a quantity related to the imaginary part of the second hyperpolarizability. [13][14][15][16][17][18][19] The quest after simple relationships between nonlinear optical properties of molecules and electronic structure parameters has a long history.…”
Section: Introductionmentioning
confidence: 99%